Dr. Dolittle - Kleinbaum, N. H.; Lofting, Hugh, 1886-1947. (New York : Bantam Doubleday Dell, 1998)
This book was made after a movie. It was a really funy movie. I havent read the book yet.
Keywords: Animals -- Fiction; Fantasy